The Effect of Concealing a Blindness Defect on the Marriage Contract - Saleh , Abdul Jalil (Islamic Sciences Journal, 2023)
The research entitled (the effect of concealing the blindness defect on the marriage contract) is summarized by submitting the topic by mentioning the sense of eyesight and distinguishing it from the rest of the senses, which made it a reason for choosing the topic as well as for the difference of jurists in considering blindness as a permissible reason for divorcing, in order not to getting conclusive evidence in this regard or an independent study of it. The research states the definition of the vocabulary of the title and the terms related to the blindness, the Blur blindness, the mute and the visual blindness, Then clarifying the opinions of the jurists on the issue and presenting their evidences , then discussing these evidences separately in order to reach the most correct opinion depending on what was strengthened by arguments from the texts and the abundant districts in mentioning what related to the sense of eyesight and what was disciplined under the rules of jurisprudence and its origins, which allows divorce as compared to the response in the sale or the defects stipulated when they are lost, At the end the most important results and recommendations have been presented.